Prevention of soil-transmitted helminth infection - Mascarini-Serra, Luciene [UNESP] (Wolters Kluwer, 2011)
Soil-transmitted helminths (STHs) form one of the most important groups of infectious agents and are the cause of serious global health problems. The most important STHs are roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura) and hookworms (Necator americanus or Ancylostoma duodenale); on a global level, more than a billion people have been infected by at least one species of this group of pathogens. This review explores the general concepts of transmission dynamics and the environment and intensity of infection and morbidity of STHs. The global strategy for the control of soil-transmitted helminthiasis is based on (i) regular anthelminthic treatment, (ii) health education, (iii) sanitation and personal hygiene and (iv) other means of prevention with vaccines and remote sensoring. The reasons for the development of a control strategy based on population intervention rather than on individual treatment are discussed, as well as the costs of the prevention of STHs, although these cannot always be calculated because interventions in health education are difficult to measure. An efficient sanitation infrastructure can reduce the morbidity of STHs and eliminates the underlying cause of most poverty-related diseases and thus supports the economic development of a country.
Keywords: Helminth infection; Prevention; Soil-transmitted Helminths; albendazole; anthelmintic agent; levamisole; mebendazole; oxantel; pyrantel; pyrantel embonate; vaccine; Ancylostoma duodenale; Ascaris lumbricoides; atopy; behavior change; climate; cost benefit analysis; disease transmission; environmental factor; environmental sanitation; feces analysis; health education; helminthiasis; human; humidity; infection control; larval stage; Necator americanus; personal hygiene; priority journal; reinfection; remote sensing; single drug dose; soil moisture; soil transmitted helminthiasis; Trichuris; worm egg